High energy fission cross sections induced by deuteron on 232Th and proton on natPb targets - Zamani, M.; Stoulos, S.; Fragopoulou, M.; Krivopustov, M. (HNPS Advances in Nuclear Physics, 2019)
Total fission cross sections induced by deuterons with energies 1.6, 2.5 and 4.0 GeV on 232Th targets and by protons on natPb targets at energy 2.0 GeV were measured during irradiations at the Nuclotron accelerator, JINR, Dubna. Using Solid State Nuclear Track detectors, the fission cross sections induced by deuterons on 232Th were determined as 1277±216, 1232±207 and 1153±198 mb, corresponding to the energies mentioned above. The total fission cross section of protons on natPb was estimated by the same method as 131±30 mb. These results were compared to the previous systematic parameterization of proton induced fission and new values for the parameters of deuteron-induce fission on actinides, 232Th and 238U and proton induced fission on natPb were deduced. Fitting results obtained for deuterons on actinides are discussed and compared to results for protons.